Heuristics for Optimization of LED Spatial Light Distribution Model - Kaljun, David; Poklukar, Darja Rupnik; Žerovnik, Janez (Informatica, 2015)
Recent development of LED technology enabled production of lighting systems with nearly arbitrary light distributions. A nontrivial engineering task is to design a lighting system or a combination of luminaries for a given target light distribution. Here we use heuristics for solving a problem related to this engineering problem, restricted to symmetrical distributions. A genetic algorithm and several versions of local search heuristics are used. It is shown that practically useful approximations can be achieved with majority of the algorithms. Statistical tests are performed to compare various combinations of parameters of genetic algorithms, and the overall results of various heuristics on a realistic dataset.